A Comparison of Classical and Pulsating Jets in Crossflow at Various Strouhal Numbers. (23rd February 2017) - Chang, Jianlong; Shao, Xudong; Li, Jiangman; Hu, Xiao
Abstract : Investigation of the classical and pulsating jet in crossflow (JICF) at a low Reynolds number (Re = 100) has been performed by the LES method based on varied velocity ratios (r = 1 4). Time-averaged particle trajectories are compared in the classical and pulsating JICF. The formation mechanism and the corresponding flow characteristics for the counter-rotating vortex pair (CRVP) have been analyzed. An unexpected "vortex tail" has been found in the JICF at higher velocity ratio due to the enhanced interactions indicated by the increased jet momentum among the CRVP, upright vortices, and shear layers. The analysis of time-averaged longitudinal vorticity including a coupling mechanism between vortices has been performed. The returning streamlines appear in the pulsating JICF, and two extra converging points emerge near the nozzle of the jet at different Strouhal numbers. The temperature profiles based on the iso-surface for the classical and pulsating JICF have been obtained computationally and analyzed in detail.